Efficacy of Different Synthetic Insecticides against Mustard Aphid (Lipaphis erysimi kalt.) (Homoptera: aphididae) on Selected Canola Cultivars - Shah, Rahim; Junaid, Khwaja; Asad Ur Rehman; Zubair, Muhammad; Ahmed, Shabir; Ahmad, Sagheer; Ijaz Ullah; Khan, Imtiaz (Indus Journal of Bioscience Research, 2025)
This study conducted at the New Developmental Farm, University of Agriculture Peshawar, during the 2021-22 crop growing season, aimed to evaluate the effectiveness of synthetic insecticides against the mustard aphid (Lipaphis erysimi K) on specific canola cultivars. Employing a Split Plot Design with three replications, the experiment identified thiamethoxam as notably efficacious in controlling mustard aphids. Following the first spray, the 'China' cultivar treated with thiamethoxam exhibited the minimum pest density (7.95), contrasting with the highest pest density observed on the 'Swabi' cultivar in the control plot (48.71). Subsequent treatments, applied upon reaching the economic threshold, revealed persistent trends. After the second spray, the 'China' cultivar treated with thiamethoxam consistently demonstrated the lowest pest density (7.64), while the 'Swabi' cultivar in the control plot exhibited the highest (48.05). Furthermore, the 'China' cultivar treated with thiamethoxam displayed maximum sub-branches (30.00) and pods per plant (90.19), along with the tallest plants (122.17 cm) and highest yield (2.92 kg/plot and 1827.1 kg/ha). Conversely, the untreated 'Swabi' cultivar showed the lowest sub-branches, pods per plant, plant height, and yield (0.42 kg/plot and 402.6 kg/ha). In summary, the integration of thiamethoxam with the 'China' cultivar yielded superior outcomes, emphasizing its potential as an effective pest management strategy in canola cultivation.